2018
DOI: 10.5897/ajb2015.15021
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the physicochemical and pasting properties of flour from three varieties of Brachystegia spp.

Abstract: The chemical compositions, functional and pasting properties of flour from three varieties of Brachystegia spp. (Brachystegia eurycoma, Brachystegia nigerica and Brachystegia kennedy) were studied. Results show that the chemical compositions of flour samples ranged from12.31 to 12.67% (protein), 1.66 to 1.72% (crude fiber), 2.06 to 2.39% (ash), 7.18 to 8.45% (fat), 3.85 to 4.75% (sugar) and 58.45 to 59.62% (starch). Functional properties such as water absorption capacity, oil absorption capacity, swelling powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The peak viscosity of the blends which is the ability of starch to swell freely before their physical breakdown [13] ranged from 651 RVU to 2766 RVU and were significantly (P<0.05) different. The highest value (2766 RVU) was recorded in blend A, follow by B (1916 RVU), C (1383 RVU), D (972 RVU) while the lowest value (651 RVU) was recorded in E. It was observed that the higher the quantity of soybean substituted in the blends the lower the peak viscosity.…”
Section: Pasting Properties Of Flour Blendsmentioning
confidence: 96%
“…The peak viscosity of the blends which is the ability of starch to swell freely before their physical breakdown [13] ranged from 651 RVU to 2766 RVU and were significantly (P<0.05) different. The highest value (2766 RVU) was recorded in blend A, follow by B (1916 RVU), C (1383 RVU), D (972 RVU) while the lowest value (651 RVU) was recorded in E. It was observed that the higher the quantity of soybean substituted in the blends the lower the peak viscosity.…”
Section: Pasting Properties Of Flour Blendsmentioning
confidence: 96%
“…Amylose content of the samples was determined using the iodine binding method established by Oke et al [11]. The amylose contents of both native and modified cocoyam starch were determined.…”
Section: Determination Of Amylose and Amylopectin Contentsmentioning
confidence: 99%
“…Te functional properties of food fours are parameters that determine its taste, favor, processing method, transportation, and storage time [34]. Diferent functional properties of A. lepidophyllus four were evaluated, and the results are presented in Table 2.…”
Section: Functional Propertiesmentioning
confidence: 99%